Delayed‐onset dementia after stroke or transient ischemic attack. Issue 11 (18th June 2016) - Mok, Vincent C.T.; Lam, Bonnie Y.K.; Wang, Zhaolu; Liu, Wenyan; Au, Lisa; Leung, Eric Y.L.; Chen, Sirong; Yang, Jie; Chu, Winnie C.W.; Lau, Alexander Y.L.; Chan, Anne Y.Y.; Shi, Lin; et al.
Abstract: Introduction: Patients surviving stroke without immediate dementia are at high risk of delayed‐onset dementia. Mechanisms underlying delayed‐onset dementia are complex and may involve vascular and/or neurodegenerative diseases. Methods: Dementia‐free patients with stroke and/or transient ischemic attack (TIA; n = 919) were studied for 3 years prospectively, excluding those who developed dementia 3 to 6 months after stroke and/or TIA. Results: Forty subjects (4.4%) developed dementia during the study period. Imaging markers of severe small vessel disease (SVD), namely presence of ≥3 lacunes and confluent white matter changes; history of hypertension and diabetes mellitus independently predicted delayed‐onset dementia after adjustment for age, gender, and education. Only 6 of 31 (19.4%) subjects with delayed cognitive decline harbored Alzheimer's disease–like Pittsburg compound B (PiB) retention. Most PiB cases (16/25, 64%) had evidence of severe SVD. Discussion: Severe SVD contributes importantly to delayed‐onset dementia after stroke and/or TIA. Future clinical trials aiming to prevent delayed‐onset dementia after stroke and/or TIA should target this high‐risk group.